ANALYSIS OF WORKING HOURS AND WORKLOAD ON WORK PRODUCTIVITY WITH JOB SATISFACTION AS A MODERATING VARIABLE AT PT PLN BINJAI CITY CUSTOMER SERVICE UNIT - Heryanto Siburian; Mesra B; Elfitra Desy Surya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effect of working hours and workload on work productivity with job satisfaction as a moderating variable at PT PLN Binjai Kota Customer Service Unit. The research method used is a quantitative approach with Partial Least Square (PLS) analysis technique. The study population was all employees of ULP Binjai Kota, with a sample of 83 respondents. The results showed that working hours had a positive and significant effect on work productivity, while workload had a negative and significant effect on work productivity. In addition, job satisfaction was proven to have a positive and significant effect on work productivity and moderated the relationship between working hours and workload with work productivity. The R Square value of 0.836 indicates that the variables of working hours, workload, and job satisfaction are able to explain the variable of work productivity by 83.6%. These findings are expected to be managerial considerations in managing working hours and workload to improve employee satisfaction and productivity within PT PLN ULP Binjai Kota.